Ethiopia: Obtaining Ethics Approval and the Role of Social Capital - Cochrane, Logan (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2018)
Ethiopia has a research ethics review system, yet few international researchers obtain approval outside of health studies that involve biological samples or medical testing. This case study outlines three types of ethics approvals in Ethiopia, and which research projects are suitable to them. In outlining these processes, I also reflect upon my own experience of obtaining ethics approval. The questions raised in this case study include concerns about accountability for international researchers as well as areas where universities and ethics bodies could improve their facilitation and support to ensure that the research conducted is approved by national authorities. I critically reflect on the role of social capital and relationships, which in my own case enabled access to information about where ethics approval could be obtained and provided significant support throughout the process. For this case study, I dawn upon my experience of applying for ethics approval in 2014, having that approval granted in 2015 and conducting research until 2016.